2010
DOI: 10.1016/j.resp.2010.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The locus coeruleus and central chemosensitivity

Abstract: The locus coeruleus (LC) lies in the dorsal pons and supplies noradrenergic (NA) input to many regions of the brain, including respiratory control areas. The LC may provide tonic input for basal respiratory drive and is involved in central chemosensitivity since focal acidosis of the region stimulates ventilation and ablation reduces CO 2 -induced increased ventilation. The output of LC is modulated by both serotonergic and glutamatergic inputs. A large percentage of LC neurons are intrinsically activated by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 107 publications
5
95
0
6
Order By: Relevance
“…The locus coeruleus (LC) is a chemosensitive area within the brain stem that is used for ventilatory control in amphibians (19). Focal acidification of the LC increases minute ventilation in vivo, while ablation attenuates the hypercapnic ventilatory response by abolishing increases in tidal volume (41).…”
mentioning
confidence: 99%
“…The locus coeruleus (LC) is a chemosensitive area within the brain stem that is used for ventilatory control in amphibians (19). Focal acidification of the LC increases minute ventilation in vivo, while ablation attenuates the hypercapnic ventilatory response by abolishing increases in tidal volume (41).…”
mentioning
confidence: 99%
“…In mammals, LC neurons are of particular interest for CO 2 challenges as >80% of these neurons respond to HA by increasing their firing rate (Filosa et al, 2002;Oyamada et al, 1998;Pineda and Aghajanian, 1997). A CO 2 -chemosensitive LC region may be conserved across vertebrates as it has been described in bullfrogs, toads and rats (Gargaglioni et al, 2010; and . As in mammals, more than 80% of LC neurons in bullfrogs are CO 2 activated , reinforcing its importance as a site for central chemoreception in anurans (Noronha-de-Souza et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at least one chemosensitive region, the locus coeruleus (LC), has been described in amphibians (toads and bullfrogs: Noronha-de-Souza et al, 2006; and mammals (reviewed in Gargaglioni et al, 2010), suggesting that CO 2 /pH chemosensitivity of the LC may be conserved across air-breathing vertebrates. Anatomical studies have identified noradrenergic cells of the LC in a variety of reptiles (Kiehn et al, 1992;Lopez et al, 1992;Smeets and González, 2000;Wolters et al, 1984), including savannah monitor lizard brainstems (Wolters et al, 1984), showing tyrosine hydroxylase-containing cell bodies in the LC neurons as observed in anurans and rats (Biancardi et al, 2008;Noronha-de-Souza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, it is clear that the ventral surface of the medulla oblongata (VMS) contains at least some of the central chemoreceptors; however, other nuclei such as the locus coeruleus have also been proposed [41,42]. At the VMS, Loeschcke and Mitchell proposed rostral, intermediate and caudal chemosensitive areas [43,44].…”
Section: Co 2 Chemosensory Transductionmentioning
confidence: 99%